Kynurenine 3‐monooxygenase mediates inhibition of Th17 differentiation via catabolism of endogenous aryl hydrocarbon receptor ligands. Issue 7 (8th May 2013) - Stephens, Geoffrey L.; Wang, Qun; Swerdlow, Bonnie; Bhat, Geetha; Kolbeck, Roland; Fung, Michael
<x xml:space="preserve">Abstract</x> The aryl hydrocarbon receptor (AhR) is a key transcriptional regulator of Th17‐cell differentiation. Although endogenous ligands have yet to be identified, evidence suggests that tryptophan metabolites can act as agonists for the AhR. Tryptophan metabolites are abundant in circulation, so we hypothesized that cell intrinsic factors might exist to regulate the exposure of Th17 cells to AhR‐dependent activities. Here, we find that Th17 cells preferentially express kynurenine 3‐monooxygenase (KMO), which is an enzyme involved in catabolism of the tryptophan metabolite kynurenine. KMO inhibition, either with a specific inhibitor or via siRNA‐mediated silencing, markedly increased IL‐17 production in vitro, whereas IFN‐γ production by Th1 cells was unaffected. Inhibition of KMO significantly exacerbated disease in a Th17‐driven model of autoimmune gastritis, suggesting that expression of KMO by Th17 cells serves to limit their continuous exposure to physiological levels of endogenous AhR ligands in vivo.